Mother Behavior in Providing Sex Education in Preschool Age - Dyah Rahmawatie Ratna Budi Utami; Ida Nur Imamah (Politeknik Negeri Jember, 2021)
Mother is the first teacher for children, considering that mothers are more intensive withpre-school age children. Parents as teachers are not only related to formal academicabilities but can be a place for discussion about everything that is experienced by children,including sex education. Teaching sex education to children is expected to prevent childrenfrom the risk of negative behavior such as sexual violence or deviant behavior because thereis education on reproductive health and protecting their personal organs. Ironically, thereis still a taboo presumption in society that makes mothers still not provide sex education tochildren. This research is a quantitative type, the test used is chi square with a sample of 32mothers. The results of the study stated that the majority of mothers had provided sexeducation to their children. There is a relationship between knowledge, attitude andinformation exposure, while there is no significant relationship between the level ofeducation and experiences of mothers during childhood with the behavior of mothers inproviding sex education to children.